Peningkatan Kapasitas UMKM Melalui Pelatihan Pengelolaan Keuangan dan Pemasaran Digital Produk UMKM Papeda Instan: Pengabdian - Oktariani, Mutiya; Fatchuroji, Acep (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) producing Papeda Instan in Merauke Regency through training in financial management and digital marketing. The activity was motivated by the low level of financial literacy and the limited utilization of digital technology in developing sago-based local enterprises. The implementation method combined classical training with hands-on practice (learning by doing) and case-based mentoring. Evaluation was conducted through pre-tests, post-tests, observations, interviews, and descriptive analysis of participants’ behavioral and business performance changes. The results showed a 45% increase in participants’ knowledge, an 85% positive shift in attitudes toward the use of digital media, and a 60% increase in sales turnover within one month after the training. The training proved effective in strengthening MSME actors’ skills in financial management using the SiApik application and in utilizing digital marketing strategies through social media and online marketplaces. Despite the limited mentoring duration and varying levels of digital literacy among participants, this program made a significant contribution to local economic empowerment and opened opportunities for the development of sustainable mentoring programs for local product-based MSMEs in South Papua.